Smart Agriculture Innovation Competition (SAIC) 2024: unveiling the technological talent and creativity of AT122 students / Nurain Johar, Ts. Mohd Hafizz Wondi dan Muhamad Nasarudin Sulaiman - Johar, Nurain; Wondi, Mohd Hafizz; Sulaiman, Muhamad Nasarudin (Corporate Communication Unit, UiTM Mukah Campus, 2024)
The Smart Agriculture Instrumentation (AGR138) course is a core subject for second-semester students of the Diploma in Herbal Production Technology (AT122) program. With the full support of the faculty, Ts. Mohd Hafizz Wondi, who serves as both the lecturer and resource person, organized the Smart Agriculture Innovation Competition (SAIC) on June 28, 2024. Moreover, there were five groups of 19 AT122 students who participated in the competition. The first-ever SAIC event showcased students’ ideas to enhance agricultural efficiency and sustainability, demonstrating their skills and knowledge in agricultural technology.